The survivor [compact disc, unabridged] - Johansen, Iris (Johansen, Iris. Eve Duncan forensics thriller., 2023)
Eve Duncan accompanies archeologist Riley Smith when they search a remote island and uncover an archeological treasure. But can they escape the island and survive long enough to reveal it to the world?